Low-pressure, high-temperature thermal bonding of polymeric microfluidic devices and their applications for electrophoretic separation - Sun, Yi (2012)
A new method for thermally bonding poly(methyl methacrylate) (PMMA) substrates has been demonstrated. PMMA substrates are first engraved by CO2-laser micromachining to form microchannels. Both channel width and depth can be adjusted by varying the laser power and scanning speed. Channel depths from 50 µm to 1500 µm and widths from 150 µm to 400 µm are attained. CO2 laser is also used for drilling and dicing of the PMMA parts. Considering the thermal properties of PMMA, a novel thermal bonding process with high temperature and low bonding pressure has been developed for assembling PMMA sheets. A high bonding strength of 2.15 MPa is achieved. Subsequent inspection of the cross sections of several microdevices reveals that the dimensions of the channels are well preserved during the bonding process. Electroosmotic mobility of the ablated channel is measured to be 2.47 × 10−4 cm2 V−1 s−1. The functionality of these thermally bonded microfluidic substrates is demonstrated by performing rapid and high-resolution electrophoretic separations of mixture of fluorescein and carboxyfluorescein as well as double-stranded DNA ladders (ΦX174-Hae III dsDNA digest). The performance of the CO2 laser ablated and thermally bonded PMMA devices compares favorably with those fabricated by other professional means.